Genetically downregulated Interleukin-6 signalling is associated with a lower risk of frailty. (27th January 2023) - Mourtzi, Niki; Georgakis, Mariosk; Ntanasi, Eva; Hatzimanolis, Alexandros; Ramirez, Alfredo; Heilmann-Heimbach, Stephanie; Grenier-Boley, Benjamin; Lambert, Jeanc; Yannakoulia, Mary; Kosmidis, Mary; Dardiotis, Efthimios; Hadjigeorgiou, Giorgos; et al.
Abstract: Background: numerous studies point towards a critical role of Interleukin 6 (IL-6) pathway in frailty pathogenesis yet the causal relationship between the two remains elusive. Methods: we selected genetic variants near the IL-6 receptor locus (IL-6R) associated with reduced C-reactive protein (CRP) levels, a downstream effector of IL-6 pathway, and we used them as genetic proxies of IL-6 signalling downregulation. We then performed a two-sample Mendelian randomisation (MR) to investigate the association with frailty status, as defined by the Frailty Index (FI) in 11, 171 individuals from the Hellenic Longitudinal Investigation of Ageing and Diet (HELIAD) study. MR analysis was repeated after excluding depression or cognition-related FI items as well as following age or sex stratification. Association with frailty was also examined using an alternative instrument, weighted on s-IL-6R levels. Replication was attempted in UK Biobank dataset. Results: genetic predisposition to IL-6 signalling downregulation, weighted on CRP levels, was associated with lower risk of frailty, inserted either as categorical (odds ratio [95% confidence interval] = 0.15 [−3.39, −0.40], P  = 0.013) or continuous variable (beta [se] = −0.09 [0.003], P  = 0.0009). Sensitivity analyses revealed similar estimates across different MR methods with no evidence for horizontal pleiotropy or heterogeneity. Results remained robust after exclusion of depression or cognition-related FI items and following sex or age stratification. Genetically increased s-IL-6R levels were negatively correlated with frailty and this finding remained significant in a meta-analysis of UK Biobank and HELIAD cohorts. Conclusion: our results support a potential causal effect of IL-6 signalling on frailty and further suggest that downregulation of IL-6 levels may reduce frailty risk.